2013
DOI: 10.1002/cbdv.201300061
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antiviral Activity of the Essential Oils of Eryngium alpinum and E. amethystinum

Abstract: The chemical compositions of the essential oils obtained by hydrodistillation of the aerial parts of Croatian Eryngium alpinum L. and E. amethystinum L. were characterized by GC-FID and GC/MS analyses. The main components identified were the sesquiterpene β-caryophyllene (19.7%) in the oil of E. amethystinum and the oxygenated sesquiterpene caryophyllene oxide (21.6%) in the oil of E. alpinum. Overall, 32 and 35 constituents were detected in the essential oils of the aerial parts of E. alpinum and E. amethysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
3
33
1
1
Order By: Relevance
“…As an example, Dunkic et al [45] studied the essential oil of E. amethystinum from Croatia and reported sesquiterpene hydrocarbons (40.1%) as the most abundant compounds, followed by lower amounts of oxygenated sesquiterpenes (19.9%) and monoterpene hydrocarbons (15.2%). In this case, the major compound was (E)-caryophyllerne (19.7%), followed by a-pinene (12.3%), a-bisabolol (7.9%), 2,3,6-trimethylbenzaldehyde (7.9%), and germacrene D (7.2%).…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…As an example, Dunkic et al [45] studied the essential oil of E. amethystinum from Croatia and reported sesquiterpene hydrocarbons (40.1%) as the most abundant compounds, followed by lower amounts of oxygenated sesquiterpenes (19.9%) and monoterpene hydrocarbons (15.2%). In this case, the major compound was (E)-caryophyllerne (19.7%), followed by a-pinene (12.3%), a-bisabolol (7.9%), 2,3,6-trimethylbenzaldehyde (7.9%), and germacrene D (7.2%).…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…Due to the inaccessibility of the material for the phytochemical research, these plants have been examined to a small extent. The presence of several phenolic acids-chlorogenic acid, rosmarinic acid, and its derivative-R-(+)-3′Oβ-d-glucopyranosyl rosmarinic acid (Le Claire et al 2005) and flavonoids-quercetin and kaempferol (Crowden et al 1969), and the essential oil (Dunkic et al 2013) was detected in the organs of ground plant. The main phenolic compounds estimated in the methanolic extract of shoots were-3,4-dihydroxyphenylacetic acid, chlorogenic and isochlorogenic acids, rosmarinic acid, as well as isoquercetin (Kikowska et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main phenolic compounds estimated in the methanolic extract of shoots were-3,4-dihydroxyphenylacetic acid, chlorogenic and isochlorogenic acids, rosmarinic acid, as well as isoquercetin (Kikowska et al 2019). Moreover, the major constituents identified by GC-FID and GC/MS in the essential oil of E. alpinum isolated by hydrodistillation of the aerial parts of the plant were caryophyllene oxide (21.6%) and α-bisabolol from oxygenated sesquiterpenes (7.8%) as well as bicyclogermecrene (11.8%) and germacrene D (10.3%) (Dunkic et al 2013). The crude extract of roots rich in phenolic acids determined by HPLC-DAD demonstrated the antioxidant activity (Le Claire et al 2005) and the essential oil of the aerial parts showed the antiphytoviral effect (Dunkic et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unavailability of the plant material, little research on this taxon was carried out. Only a few papers indicated the presence of phenolic acids, flavonoids and the essential oil in the organs of in vivo plants [3][4][5][6][7]. The identification of flavonoids, namely quercetin and kaempferol, in leaves of alpine eryngo was described by Crowden et al [3].…”
Section: Introductionmentioning
confidence: 99%